Arbuscular Mycorrhizal Symbiosis Alleviates Salt Stress in Black Locust through Improved Photosynthesis, Water Status, and K+/Na+ Homeostasis - Chen, Jie; Zhang, Haoqiang; Zhang, Xinlu; Tang, Ming (Frontiers in Plant Science, 2017)
Soil salinization and the associated land degradation are major and growing ecological problems. Excess salt in soil impedes plant photosynthetic processes and root uptake of water and nutrients such as K+. Arbuscular mycorrhizal (AM) fungi can mitigate salt stress in host plants. Although numerous studies demonstrate that photosynthesis and water status are improved by mycorrhizae, the molecular mechanisms involved have received little research attention. In the present study, we analyzed the effects of AM symbiosis and salt stress on photosynthesis, water status, concentrations of Na+ and K+, and the expression of several genes associated with photosynthesis (RppsbA, RppsbD, RprbcL and RprbcS) and genes coding for aquaporins or membrane transport proteins involved in K+ and/or Na+ uptake, translocation or compartmentalization homeostasis (RpSOS1, RpHKT1, RpNHX1 and RpSKOR) in black locust. The results showed that salinity reduced the net photosynthetic rate, stomatal conductance and relative water content in both non-mycorrhizal (NM) and AM plants; the reductions of these three parameters were less in AM plants compared with NM plants. Under saline conditions, AM fungi significantly improved the net photosynthetic rate, quantum efficiency of photosystem II photochemistry and K+ content in plants, but evidently reduced the Na+ content. AM plants also displayed a significant increase in the relative water content and an evident decrease in the shoot/root ratio of Na+ in the presence of 200 mM NaCl compared with NM plants. Additionally, mycorrhizal colonization upregulated the expression of three chloroplast genes (RppsbA, RppsbD and RprbcL) in leaves, and three genes (RpSOS1, RpHKT1 and RpSKOR) encoding membrane transport proteins involved in K+/Na+ homeostasis in roots. Expression of several aquaporin genes was regulated by AM symbiosis in both leaves and roots depending on soil salinity. This study suggests that the beneficial effects of AM symbiosis on the photosynthetic capacity, water status and K+/Na+ homeostasis lead to the improved growth performance and salt tolerance of black locust exposed to salt stress.